Juvenile crime and justice - Chambliss, William J. (Thousand Oaks, CA : SAGE, 2011)
Presents arguments both in favor of and opposed to various treatments, programs, and punishments, examining issues such as youth curfews, juveniles in adult courts, legal representation for juveniles, juvenile boot camps, group homes, and out-of-home placement.
19. Serious and violent juvenile offenders -- Historical developments -- Risk and violence -- Individual risk -- System response -- Pro: benefits of predicting serious offenders -- Con: drawbacks of predicting serious offenders -- 20. Treatment and rehabilitation -- Evolution of treatment and rehabilitation approaches -- Treatment of youths in general -- Treatment of youths in the Justice Sector -- Culpability or treatment amenability: youths versus adults -- How to treat -- Principles of effective treatment -- Whom to treat -- Pro: arguments in support of treatment -- Treatment does work -- Con: arguments against treatment -- Distributive justice -- The future of treatment and rehabilitation.
Includes bibliographical references and index.
Presents arguments both in favor of and opposed to various treatments, programs, and punishments, examining issues such as youth curfews, juveniles in adult courts, legal representation for juveniles, juvenile boot camps, group homes, and out-of-home placement.
Keywords: Juvenile delinquency; Crime; Law enforcement; Corrections; Criminal justice, Administration of; Corrections; Crime; Criminal justice, Administration of; Juvenile delinquency; Law enforcement